#TITLE_ALTERNATIVE# - SITORUS (NIM 10107086); Pembimbing : Dr. Udjianna S.Pasaribu, WULANDARI
Viterbi algorithm is a method to solve main problem in Hidden Markov Model, which is to find the most probable sequence of hidden states. This algorithm has some benefit such as short time needed, systematic step, and the decision of algorithmÃ‚Â’s output is based on the whole sequence. However, this algorithm only can find the most probable sequence of hidden states. Thus, the other probable hidden state can not be showed in this algorithm. For example, data of gen plasmodium falciparum CDS will be taken for finding its hidden state (exon and intron). MATLAB R2010a software will be used to proceed viterbi agorithm.